2008
DOI: 10.1007/s00247-008-1019-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI and US findings of subcutaneous fat necrosis of the newborn

Abstract: Subcutaneous fat necrosis of the newborn (SCFN) is an uncommon, benign disorder found in full-term or post-mature neonates. It usually presents in neonates who have experienced perinatal difficulty such as asphyxia, peripheral hypoxemia, hypothermia, meconium aspiration or trauma. We present a newborn with abnormal findings on MRI and US within the axilla, neck, and abdominal walls that were pathologically proved via biopsy to be subcutaneous fat necrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…To our knowledge there have been no reports of SCFN after brief TH (48 hours instead of 72 hours of standard cooling protocol), and no US studies of SCFN due to TH. Vasireddy et al performed ultrasonography in a newborn with no history of TH, demonstrating hyperechoic retroperitoneal fat necrosis in the acute phase. Our findings on echographic examination are similar to those that Fernando et al colleagues, who studied subcutaneous fat necrosis in adults, observed.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there have been no reports of SCFN after brief TH (48 hours instead of 72 hours of standard cooling protocol), and no US studies of SCFN due to TH. Vasireddy et al performed ultrasonography in a newborn with no history of TH, demonstrating hyperechoic retroperitoneal fat necrosis in the acute phase. Our findings on echographic examination are similar to those that Fernando et al colleagues, who studied subcutaneous fat necrosis in adults, observed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 One case with thoracic and abdominal involvement along with subcutaneous fat necrosis after asphyxia is described in the literature. 3 This case is reported for its didactic radiologic findings concordant with visceral fat necrosis besides a mild subcutaneous one, which is very rarely observed in patients with asphyxia who underwent cooling. With this case, we wanted to draw attention to the possible presence of visceral fat necrosis together with subcutaneous necrosis, regardless of its severity.…”
mentioning
confidence: 71%
“…Imaging tests are usually not required for diagnosis, although they may play an important role in excluding other differential diagnoses. 9,10 The diagnosis can be confirmed by aspiration cytology or skin biopsy. The histology is typical, showing areas of fat necrosis surrounded by a granulomatous reaction consisting of histiocytes, macrophages and giant cells and associated with calcification foci.…”
Section: Discussionmentioning
confidence: 99%